2003
DOI: 10.1007/s00439-003-0950-4
|View full text |Cite
|
Sign up to set email alerts
|

SONIC HEDGEHOG mutations causing human holoprosencephaly impair neural patterning activity

Abstract: Holoprosencephaly (HPE) is a common forebrain malformation associated with mental retardation and craniofacial anomalies. Multiple lines of evidence indicate that loss of ventral neurons is associated with HPE. The condition is etiologically heterogeneous, and abnormalities in any of several genes can cause human HPE. Among these genes, mutations in SONIC HEDGEHOG (SHH) are the most commonly identified single gene defect causing human HPE. SHH mediates a number of processes in central nervous system developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 54 publications
1
15
0
Order By: Relevance
“…Especially SHH has been implicated as central in the process of determining the identity of the progenitor cells of the spinal cord. Mutations of SHH in human have been noted as causative of holoprosencephaly (Roessler et al, 1996) and also to impair neural patterning activity (Schell-Apacik et al, 2003). The intensity levels of SHH were below the detection limit on the gene chips, and thus we were not able to deduce any changes in expression between the LCCS patients and controls.…”
Section: Discussionmentioning
confidence: 78%
“…Especially SHH has been implicated as central in the process of determining the identity of the progenitor cells of the spinal cord. Mutations of SHH in human have been noted as causative of holoprosencephaly (Roessler et al, 1996) and also to impair neural patterning activity (Schell-Apacik et al, 2003). The intensity levels of SHH were below the detection limit on the gene chips, and thus we were not able to deduce any changes in expression between the LCCS patients and controls.…”
Section: Discussionmentioning
confidence: 78%
“…Expression of Shh has been reported in human embryonic ventral spinal cord and mesencephalon (Hajihosseini et al, 1996; Orentas et al, 1999), and Shh mutation is related to brain defects such as holoprosencephaly or cyclopia (Schell-Apacik et al, 2003). Experimentally, these defects can be induced by the selective Shh inhibitor cyclopamine, a steroidal alkaloid known to interrupt Shh signaling by binding to its co-receptor Smoothened (Incardona et al, 1998).…”
Section: Resultsmentioning
confidence: 99%
“…Similar to Shh [59], mutations in the homeodomain of the human Six3 gene cause holoprosencephaly and are associated with midline facial cleft - tessier cleft 14 [60]. In mice, it has been shown that Six3 protein increases expression of Ccnd1 protein [61], which is directly related to TGFβ signaling (Figure  6).…”
Section: Discussionmentioning
confidence: 99%